The Legal System For Rights of an Economic nature for people with disabilities in Iraq - Khalil Matar, Lect. Hussein (Basra studies journal, 2025)
The research focused on examining the legal framework governing the economic rights of persons with disabilities. It began by identifying key economic challenges faced by this group to pinpoint areas of deficiency. The study then highlighted the essential standards that should be applied to these rights, with particular emphasis on the principles of accessibility and quality standards. Through an analysis of legal provisions concerning various economic rights—most notably the right to work, employment, and access to appropriate vocational training and rehabilitation—the research compared legal texts with practical realities to diagnose underlying issues and propose suitable solutions. A significant gap was observed between legal provisions and their practical implementation, assessed in light of relevant economic rights standards for persons with disabilities.